Evaluation of myocardial reperfusion in patients undergoing cangrelor supported primary PCI for STEMI. (14th October 2021) - Muraca, I; Pennesi, M; Mattesini, A; Migliorini, A; Carrabba, N; Scudiero, F; Virgili, G; Bruscoli, F; Pontecorboli, G; Marchionni, N; Di Mario, C; Valenti, R
Abstract: Background: Optimal myocardial reperfusion is the main goal of pharmaco-invasive treatment in STEMI patients. Cangrelor is a new intravenous P2Y12 inhibitor, mainly used in intra-procedural PCI setting of STEMI patients. Intracoronary cangrelor bolus application results in high local drug concentrations and may be more effective than a standard intravenous bolus. Aim: This study aims to investigate the potential benefits of intracoronary versus intravenous cangrelor bolus in STEMI patients undergoing to primary PCI (p-PCI). Materials and methods: Overall, 71 consecutive STEMI patients undergoing p-PCI were treated with intracoronary (n=37) or intravenous (n=34) bolus cangrelor administration with subsequent 2-hour intravenous infusion. The primary end point was ST-elevation reduction (STR) ≥50% at 30 minutes and at 24 hours after p-PCI. Secondary end points were STR ≥70% at 30 min after p-PC, TIMI frame count, and the QT dispersion (QTd). Moreover, stent thrombosis, bleeding events according to BARC classification, and 30-day mortality have been evaluated as safety explorative end points. Results: STEMI patients treated with intravenous Cangrelor bolus had a higher rate of STR ≥50% either at 30 minutes (72% vs. 45%; p=0.033) or at 24 hours after p-PCI (87.1% vs. 63.6%; p=0.030) as compared to patients treated with intracoronary Cangrelor bolus; similarly, STR ≥70% at 30 minutes was more frequent in the intravenous bolus group as compared to intracoronary one (67% vs. 29% p=0.02). Furthermore, multivariable analysis demonstrated that intravenous Cangrelor bolus administration was an independent predictor of STR ≥50% (OR 3.586; 95% CI 1.134 to 11.335; p=0.030). No differences according to the TIMI frame count and the QTd were found. No stent thrombosis were observed at 30 days. The incidence of mortality and bleeding events (BARC 3–5) were comparable among study groups (30 days-death: 2.9% vs 5.4%, p=0.606; BARC 3–5 bleedings: 17.6% vs 13.5% p=0.630). Conclusion: Intravenous coronary bolus administration of cangrelor in primary PCI is superior to intracoronary treatment with respect to extent of microvascular obstruction, and perfusion. FUNDunding Acknowledgement: Type of funding sources: None.